RAMIFICATIONS OF COVID-19 ON THE JOHANNESBURG STOCK EXCHANGE (JSE) AND THE NAIROBI SECURITIES EXCHANGE (NSE) - Kamoet, Lilly (My University, 2022)
The study sought to determine the effect of the Covid-19 pandemic on the Kenyan and South African financial stock markets. The two stock markets analysed in the research were Nairobi Securities Exchange (NSE) and the Johannesburg Stock Exchange (JSE). Events that were studied in this research to determine the impact on the stock markets was: the announcement of the first Covid-19 case in Kenya, announcement of the first Covid-19 case in South Africa and the announcement by WHO declaring Covid-19 to be a pandemic. The rise of the pandemic shook the major sectors that drive economic well-being of the society hence impacting the stock markets. Event study methodology was used in this research. The findings from the research revealed that the stock markets exhibited a significantly high volatility days after the announcement of the first case of Covid-19 in the country. The alarming progression of the pandemic also caused fear and panic among investors. In comparison to the developed economies, the healthcare system in the two countries were insufficiently equipped to contain the spread of the virus therefore causing rapid spread of the virus hence disastrous economic losses. The findings from the research con-tribute to the financial literature on the impact of Covid-19 on the stock market particularly in the African markets.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance